Reviewing the use of ventricular assist devices in the elderly: where do we stand today?. (2nd January 2018) - Nair, Nandini; Gongora, Enrique
ABSTRACT: Introduction : Implantation of left ventricular assist devices (LVADS) in older patients appears to be an attractive option in the wake of donor shortage and increasing incidence and prevalence of end stage heart failure. Since the inception of the artificial heart program half a century ago tremendous progress in research and development has led to utilization of more sophisticated devices. VADs have therefore emerged as a successful therapy for extending life with meaningful quality. Areas covered : This review will address the use of LVADS as a bridge to transplantation, destination therapy and comparison of LVAD therapy with alternate list heart transplantation in the elderly population. Expert commentary : Age >70 years is an important aspect when assessing LVAD risk, but other characteristics appear to be better predictors of LVAD survival. Elevated pre-operative creatinine, bilirubin and ischemic etiology predispose to a higher risk of mortality. Creatinine has been shown to be a very powerful predictor in post LVAD survival. Based on the existing literature, the authors suggest an algorithm which could be useful when evaluating patients for LVAD implantation.